Risk factors of cerebral complications after cardiac surgery - L. M. Tibekina; E. G. Smertina; V. D. Zolotov; A. O. Zaitseva; A. P. Kretsu; M. S. Stolyarov; M. S. Kamenskikh; M. V. Starosotskaya; D. V. Shmatov (Вестник хирургии имени И.И. Грекова, 2017)
OBJECTIVE. The authors defined the risk factors of cerebral complications after cadiosurgical operations. MATERIAL AND METHODS. The patients with ischemic heart disease who underwent coronary artery bypass grafting (CABG) were included in the first group (n=189) 132 (69,8 %) men and 57 (30,2 %) women aged 62,5 ± 8,3 years old. The patients who underwent reconstructive surgery of the heart valves were in the second group (n=50) and numbered 34 (68 %) men and 16 (32 %) women aged 63,1 ± 7,7 years old. The operations on valves were performed under conditions of extracorporeal circulation in the Center of Cardiosurgery and Interventional Cardiology of St. Petersburg Multidisciplinary Center. RESULTS. The research showed that the proportion of severe cerebral complications such as acute stroke and delirium was equal to 7,4 % in patients with coronary artery bypass grafting, while in group of patients with valvular pathology it numbered 14,0 %. The proportion of patients with delirium was 5,8 % in the first group and it consisted of 12 % in the second group. The number of patients with stroke was 1,58 % in the first group and it counted 2,0 % in the second group. Chronic cerebrovascular failure, stroke in the anamnesis, fibrillations of auricles and post-infarction cardiosclerosis were the leading risk factors of acute stroke development in early postoperative period. CONCLUSIONS. There was noted that such risk factors as postinfarction cardiosclerosis, stroke in the anamnesis and also the constrictive atherosclerosis of brachiocephalic trunk were associated with the group of patients who had cerebral complications after CABG operation. The proportion of patients with fibrillations of auricles (paroxysmal form) and a low left ventricular ejection fraction was higher in group of patients who underwent reconstructive surgery of the heart valves. The frequency of tobacco smoking was high among patients in both subgroups (77 % and 57,1 %).